Ziziphi Spinosae Semen: A Natural Herb Resource for Treating Neurological Disorders - Zhang, Mei; Liu, Jinrui; Zhang, Yanqing; Xie, Junbo (Current Topics in Medicinal Chemistry, 2022)
Neurological disorders generally have the characteristics of occult onset and progressive development, which can do some serious damage to the human body in the aging process. It is worth noting that traditional medicine can potentially prevent and treat such diseases. Ziziphi Spinosae Semen (ZSS), the seeds of Ziziphus jujuba var. spinosa, has a long clinical history for sleep regulation. In recent years, ZSS has been proved to exhibit various types of neuroprotective activity, such as sleep improvement, antidepressant, anti-anxiety, memory improvement, etc. It has become a popular natural product due to its many inherently available compounds that demonstrate medicinal and pharmacological importance. This paper reviews the main components and their metabolic transformation processes, highlights the various neurofunctional regulation activities and the mechanisms of ZSS, providing a theoretical basis for further research and clinical application of this natural medicine.
Keywords: Ziziphi spinosae semen